Four-Year Outcomes of Small Incision Lenticule Extraction for Extreme High Myopia and Myopic Astigmatism - Xia, Fei; Qin, Bing; Shang, Jianmin; Chen, Zhuoyi; Zhou, Xueyi; Zhao, Jing; Wang, Xiaoying; Zhou, Xingtao (Frontiers in Medicine, 2020)
Purpose: To evaluate the long-term safety, efficacy, predictability, and stability of small incision lenticule extraction (SMILE) for the treatment of high myopia and myopic astigmatism greater than -10.0 D. Methods: This was a prospective study that incorporated 35 consecutive patients (35 eyes) undergoing SMILE from September 2015 to March 2016. These patients had a mean preoperative spherical equivalent refraction of -10.06±0.64 D. Patients were followed over a four-year period and assessed for outcomes including uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), manifest refraction, and corneal topography. Results: At four years post-SMILE, respective efficacy and safety indices were 1.01±0.19 and 1.07±0.15. In total, 97% of operated eyes achieved an UDVA of 20/25 or better. ≥ 1 line was gained for 9 eyes (26%), with 25 eyes (71%) remained stable. 24 (69%) and 33 (94%) eyes, respectively, were within ± 0.50 D and ± 1.0 D of target refraction. From three months to four years postoperatively, a mean refractive regression of -0.22 D (-0.06 D per year) was detected, whereas no significant changes in mean corneal back curvature or posterior central elevation were detected (P=0.617 and 0.754, respectively). We detected significant increases in higher-order aberrations (HOAs) of the anterior and total cornea (all P<0.001), with spherical aberrations and vertical coma being particularly common, whereas posterior corneal HOA remained fairly stable (all P<0.05). Conclusion: SMILE is a safe, effective, predicable and stable means of correcting high myopia and myopic astigmatism over a four-year postoperative period.